2012
DOI: 10.1016/j.quaint.2012.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Subglacial tunnel valleys in the Alpine foreland - an example from Bern, Switzerland

Abstract: The morphology of the Alpine and adjacent landscapes is directly related to glacial erosion and associated sediment transport. Here we report the effects of glacio-hydrologic erosion on bedrock topography in the Swiss Plateau. Specifically, we identify the presence of subsurface valleys beneath the city of Bern and discuss their genesis. Stratigraphic investigations of more than 4,000 borehole data within a 430 km 2-large area reveal the presence of a network of [200 m-deep and 1,000 m-wide valleys. They are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Glasser and Bennett, 2004), often called Nye channels (N-channels; Weertman, 1972) and kilometre-scale tunnel valleys (e.g. Ó Cofaigh, 1996;Glasser and Bennett, 2004;Jørgensen and Sandersen, 2006;Dürst Stucki et al, 2010;Kehew et al, 2012), and more recently its role has been invoked as a necessary mechanism in the carving and deepening of inner gorges (Dürst Stucki et al, 2012;Jansen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Glasser and Bennett, 2004), often called Nye channels (N-channels; Weertman, 1972) and kilometre-scale tunnel valleys (e.g. Ó Cofaigh, 1996;Glasser and Bennett, 2004;Jørgensen and Sandersen, 2006;Dürst Stucki et al, 2010;Kehew et al, 2012), and more recently its role has been invoked as a necessary mechanism in the carving and deepening of inner gorges (Dürst Stucki et al, 2012;Jansen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…10). Detailed studies of the Alpine foreland showed a similar impact of glaciation with deep gorges eroded by sub-glacial fluids beneath the ice sheets from the Alps (Dürst Stucki et al, 2010Stucki et al, , 2012.…”
Section: The Esf Eurocores Topo-europe Programmentioning
confidence: 99%
“…Korup and Schlunegger (2007) and Montgomery and Korup (2011) suggest that inner gorges throughout the Alps would have been successively preserved and deepened throughout multiple glacial/interglacial cycles. Furthermore, Duerst- Stucki et al (2010; found that subglacial meltwater under pressure created a tunnel valley network under the Aar glacier in the vicinity of Berne, Switzerland. They also used a similar mechanism to explain the formation of inner gorges that cut across conglomerate beds with low erodibilities.…”
Section: Is the Incision Of The Entlen Inner Gorge Post-glacial Or Not?mentioning
confidence: 99%
“…The erosional work of glaciers also result in the deposition of large amounts of unconsolidated glacial till, which comprises a very wide range of clast sizes. Fluvial processes acting either during glaciations (as subglacial meltwater, Duerst-Stucki et al, 2010 or upon glacial retreat (Montgomery and Korup, 2011) lead to incision into the glacially-sculpted topography. This occurs primarily by the propagation of transient erosional waves (testified by pervasive knickzones), frequently resulting in the formation of inner gorges (Whipple, 2009), where incision interacts with hillslope processes (Gallen et al, 2011), and by the evacuation of unconsolidated glaciogenic material Van den Berg and Schlunegger, 2012).…”
Section: Introductionmentioning
confidence: 99%